2021
DOI: 10.21203/rs.3.rs-131323/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency of metabolic syndrome and insulin resistance in epileptic patients treated with sodium valproate or carbamazepine monotherapy: A Case-Control Study 

Abstract: Background Metabolic syndrome (MetS) represents a collection of metabolic risk factors such as obesity, dyslipidemia, hyperglycemia, and hypertension. Medications can increase the incidence rate of MetS and insulin resistance (IR). Objective This study aims to evaluate the effects of Carbamazepine (CBZ) or Valproate (VPA) as monotherapy on the development of MetS and IR in the adult Iranian epileptic patients. Methods In this observational analytic case-control study, 80 epileptic patients were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Likewise, BMI was significantly associated with MS in both the IDF and ATP-III criteria. This is consistent with the studies conducted in Estonia [ 22 ], Iran [ 45 ] and Japan [ 38 ]. The result could be explained in light of the contribution of increased body weight to central obesity, which leads to the accumulation of fat in the body.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, BMI was significantly associated with MS in both the IDF and ATP-III criteria. This is consistent with the studies conducted in Estonia [ 22 ], Iran [ 45 ] and Japan [ 38 ]. The result could be explained in light of the contribution of increased body weight to central obesity, which leads to the accumulation of fat in the body.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, PCOS has been associated with co-morbidities, such as type 2 diabetes, dyslipidemia, hyperinsulinemia, insulin resistance, obesity, infertility, and galactorrhea 31 . A study on Finnish women demonstrated that approximately 60% of individuals who received VPA exhibited biochemical and clinical changes related to PCOS 32 . One common side effect of PCOS is weight gain that could result from mitochondrial inhibition in response to oxidative metabolites 33 .…”
Section: Discussionmentioning
confidence: 99%
“…9,[27][28][29] Parenthetically, the relationship between valproate use and risk of NAFLD is not established, although several studies report such an association. 30,31 Moreover, the included studies remained limited in discerning the difference between the association of BD-I and BD-II with NAFLD, respectively.…”
Section: Bipolar Disordermentioning
confidence: 99%